KEKUDUSAN HIDUP MENURUT 1TESALONIKA 4:1-8 RELEVANSINYA TERHADAP PEMAHAMAN PEMUDA DI GKAI SUNTER - Enny Irawati (Jurnal Teologi Biblika, 2020)
This research is intended to analyze in depth and objectively the understanding of GKAI Sunter youth about holiness according to 1 Thessalonians 4: 1-8). This study uses qualitative research methods in taxonomic analysis, using inductive interpretation of biblical research based on the naturalistic paradigm. Data was collected through participant observation using holiness based written interviews according to 1 Thessalonians 4: 1-8. The questions used are based on an analysis with three sub focus (1) Life that pleases God, (2) Life in holiness, (3) Life doing God's will. The samples used were 7 young men from the age of 16-23 years, male and female sex. The results showed that the youth of GKAI Sunter had a good understanding of holiness. The highest understanding that in Christian marriage is monogamous and there should be no divorce, continued with the understanding that maintaining holiness means not having sex outside marriage and the lowest is an understanding of the type of fornication that must be shunned, namely murder and obscenities.